Uma análise dos exercícios com sílabas em Diários de Classe de professoras alfabetizadoras (1973 - 2010) - Lima, Gisele Ramos (2013)
The present Master Degree Paper presents an analysis about the types and the recurrence of activities involving syllables, observed in 68 Class Diaries that belonged to literacy teachers from a period between the years of 1973 and 2010. These Diaries belong to the collection from the Research Group HISALES, linked to the Universidade Federal de Pelotas /Faculdade de Educação. The objective of the research is to understand why the activities with syllables are recurring and were kept during the studied period. This study is inserted in the field of history of the literacy, which in Brazil, according to Maciel (2003), groups mainly the problematization around two axis: os métodos de leitura e escrita e os manuais escolares cartilhas ( The methods of writing and reading and the school manuals primer ) (MACIEL, 2003, p. 233). The nature of this research is qualitative (LÜDKE & ANDRÉ, 1986), having as epistemological model the evidentiary paradigm proposed by Ginzburg (2011), that presents as presupposition the search for traces , clues , evidences in the researched documents, aiming to find in the details what is possible to consider as relevant elements to answer the questions from the research. In relation to the results found, among other observed questions, it was possible to contrast the predominance of traditional methods of literacy in the planning registered in the Diaries. In relation specifically to the work with syllables, the most frequent activities worked by the literacy teachers were those that privilege the copy and the memorization of such structure. The study also showed that the divulgation of studies of the Psicogênese da Língua Escrita (FERREIRO; TEBEROSKY, 1985) seems to have had little influence in the planning of great part of the researched Diaries. Such results aim to the need that the activities with syllables must be rethought and resignified, considering the studies about the Psicogênese da Língua Escrita and other studies in the field that reference the writing as a notational system and not a code to be deciphered.